Nomenclatural updates in Dyschoriste and Hygrophila (Acanthaceae) - Monteiro, Fernanda Kalina Da Silva; Daniel, Thomas F.; de Melo, José Iranildo Miranda (Phytotaxa, 2020)
Dyschoriste and Hygrophila (Acanthaceae: Ruellieae) comprise two complex and morphologically similar genera with numerous as yet unresolved nomenclatural issues. In this study, the names D. erythrorhiza and Homotropium erythrorhyzum var. latifolium are lectotypified and H. erythrorhyzum var. latifolium and H. angusta are reduced to synonymy under D. erythrorhiza and H. guianiensis, respectively. Hygrophila oblongifolia is shown to be an illegitimate name and synonymous with H. acutangula. A new name, H. nordestina, is proposed for H. sessilifolia.